Life cycle analysis of shea butter biodiesel using GREET software. - Quansah, Solomon (Kansas State University, 2012)
In this study, life cycle analysis (LCA) of shea butter biodiesel from Well-to-Pump (WTP) is considered utilizing information gathered from Anuanom Industrial Bio Products Ltd. (AIBP) in Ghana, West Africa. The information presented in this report starts with shea plant cultivation, proceeds through harvesting of shea fruits, extraction of shea butter from shea kernels, and finishes with the production of shea butter biodiesel via homogenous acid–alkali transesterification reactions utilizing methanol. After researching the conversion of shea butter to biodiesel, the GREET software was explored as a tool to perform LCA. Shea butter is an excellent alternative feedstock to produce biodiesel on an industrial scale. Though research into shea plant cultivation and subsequent conversion into biodiesel in Ghana has not received formal attention, it has huge potential in the biodiesel industry. The tree originates in Africa and is tropical and drought-resistant. Although even some basic agronomic characteristics of shea butter are not yet fully understood, the plant enjoys a booming interest, which may hold the risk of unsustainable practice. The GREET software from the Argonne National laboratory of the US Department of Energy (DOE) was used in LCA. The software is a very useful tool specifically designed for LCA focused on energy and emissions of different production processes, including biodiesel production. This software is managed by DOE research laboratory and is made available for public use. The GREET software allow users perform many existing fuel production processes. To perform an LCA on shea butter biodiesel which is a new feedstock to the GREET software, some of the requisite information, and data input has to be sent to the Argonne National Laboratory personnel for input. For a new biodiesel feedstock such as shea butter which is not part of the GREET software database, it is important to work with the Argonne National laboratory to perform the LCA.
Keywords: Biodiesel LCA; GREET LCA; Chemical Engineering (0542)